The North American tree‐ring fire‐scar network. Issue 7 (12th July 2022) - Margolis, Ellis Q.; Guiterman, Christopher H.; Chavardès, Raphaël D.; Coop, Jonathan D.; Copes‐Gerbitz, Kelsey; Dawe, Denyse A.; Falk, Donald A.; Johnston, James D.; Larson, Evan; Li, Hang; Marschall, Joseph M.; Naficy, Cameron E.; et al.
Abstract: Fire regimes in North American forests are diverse and modern fire records are often too short to capture important patterns, trends, feedbacks, and drivers of variability. Tree‐ring fire scars provide valuable perspectives on fire regimes, including centuries‐long records of fire year, season, frequency, severity, and size. Here, we introduce the newly compiled North American tree‐ring fire‐scar network (NAFSN), which contains 2562 sites, >37, 000 fire‐scarred trees, and covers large parts of North America. We investigate the NAFSN in terms of geography, sample depth, vegetation, topography, climate, and human land use. Fire scars are found in most ecoregions, from boreal forests in northern Alaska and Canada to subtropical forests in southern Florida and Mexico. The network includes 91 tree species, but is dominated by gymnosperms in the genus Pinus . Fire scars are found from sea level to >4000‐m elevation and across a range of topographic settings that vary by ecoregion. Multiple regions are densely sampled (e.g., >1000 fire‐scarred trees), enabling new spatial analyses such as reconstructions of area burned. To demonstrate the potential of the network, we compared the climate space of the NAFSN to those of modern fires and forests; the NAFSN spans a climate space largely representative of the forested areas in North America, with notable gaps in warmer tropical climates. Modern fires are burning in similar climate spaces as historical fires, but disproportionately in warmer regions compared to the historical record, possibly related to under‐sampling of warm subtropical forests or supporting observations of changing fire regimes. The historical influence of Indigenous and non‐Indigenous human land use on fire regimes varies in space and time. A 20th century fire deficit associated with human activities is evident in many regions, yet fire regimes characterized by frequent surface fires are still active in some areas (e.g., Mexico and the southeastern United States). These analyses provide a foundation and framework for future studies using the hundreds of thousands of annually‐ to sub‐annually‐resolved tree‐ring records of fire spanning centuries, which will further advance our understanding of the interactions among fire, climate, topography, vegetation, and humans across North America.